Council Directive 93/13/EEC on unfair terms and its development by the Court of Justice of the European Union. Contributions to the construction of a protective discipline and open questions - Carballo Fidalgo, Marta (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This paper analyses the essential aspects of the European regime on unfair terms, marked by the abundant jurisprudence of the Court of Justice in the interpretation of Directive 93/13/EEC. In particular, the scope of application of the regulation, the notions of unfair term and transparency and the consequences of the declaration of the unfair nature of a term are studied.